The Language Style of PKK Women in Promoting Telang Tea as the Main Product of the Karangbong Community - Devi Citra Ayu,; Khoiriyah, Aminatul; Qolby, Natasya Eolin; Antikasari, Desy; Suwandhi, Ega Aryaputra; Asteria, Prima Vidya (Proceeding of International Joint Conference on UNESA, 2024)
Language is a medium for communication that is used to convey information to the interlocutor in the form of letters, words, punctuation marks, and sentences. In a language, there is a style of language that is used to beautify a sentence like the people of Karangbong, especially PKK women, who use metaphorical language to promote Telang Herbal Tea (TETEH) through Instagram. The metaphor style is to compare something without using conjunctions as a comparison. In this case, it can be interpreted that the metaphor has a figurative meaning or not the actual meaning. Therefore, this article aims to find out the language styled by PKK Karangbong Village women in promoting Telang products and promotions on e-commerce platforms. The method used in this article is qualitative with a descriptive-analytic approach. The research subjects were PKK mothers in Karangbong Village. The research material object is TETEH product packaging and TETEH product advertisements on the account @pkmpm.healthteamom, while the formal object is language style and function. The type of data in this study is meaningful data in the form of words, phrases, and sentences that reflect the types and meanings of the figurate language contained on the TETEH product packaging and the Instagram account @pkmpm.healthteamom. The source of this research data is secondary data—techniques used in collecting data with documentation, reading, and re-recording.